Opening theory as an innovative model of the development strategy of industrial companies - Arefyeva, O.; Prokhorova, V.; Chebanova, N.; Khaustova, V.; Mushnikova, S. (International Journal of Engineering and Technology, 2018)
The modern state of the national economy requires significant changes at all levels. Industrial companies as one of the main elements of the national economy exert a great influence on formation of the well-being. So, it is industrial companies that should be developed. However, development is only possible provided there is a relevant control system, and in the modern economic conditions, innovative management forms and techniques for the development of industrial companies should be implemented. Together with multiple current management forms and techniques for industrial companies, implementing an innovative form that is based on opening theory borrowed from the chess game is proposed. Using this theory that unites mathematical and gaming methods of the management of development of an industrial company, an innovative model of the development strategy could be formed that would take into account antagonisms of socioeconomic relations. Opening theory has distinct advantages in the formation of the innovative development strategy for an industrial company. It takes into account multiples factors which influence the contradictions in the socioeconomic relations choosing the optimal decision by the min antagonism criterion in the initial phase. A material deficiency of the mathematical formalization of the socioeconomic problems is the result of their qualitative novelty and complexity. Â Â